Analisis Penampilan Teknik Bermain Argentina Dan Brasil Dalam Laga Final Copa America Tahun 2021 Di Maracana Brasil - Dicky Fatur Rohman; Achmad Widodo; Mokhamad Nur Bawono; Fatkur Rohman Kafrawi (LPPM Politeknik Pratama, 2024)
Football is a global sport that has many fans. This sport is easy to follow, it can be seen from the euphoria of the supporters of each team. But since the pandemic, the euphoria has begun to have very few followers. The 2021 Copa America was supposed to be held in 2020, but was postponed by a year due to the pandemic. Finally, CONMEBOL confirmed the tournament would take place at the Maracanã. The purpose of this study is to understand the effectiveness of Argentina and Brazil in the Copa America 2021 Final match which the final score was 1-0 for Argentina's victory. The research method used is quantitative descriptive. The source of this research data comes from the video of the 2021 Copa America Final match. The results of research in the Copa America 2021 Final match Brazil made accurate passes as many as 423 (86%) and inaccurate 65 (14%), successful shooting 2 (28%), successful dribbling as much as 18 (54%), control obtained 316 (97%) and precise heading as much as 11 (65%). Brazil's playing technique should have been favored but could not break Argentina's goal. Argentina with a 4-4-2 formation is able to withstand Brazil's attack using a 4-3-3 formation which should have many opportunities options. After an analysis of the performance of the Brazilian National Team's playing techniques, a good conclusion was obtained, but the existing advantages were not utilized optimally and the opportunities obtained will be used as material for team evaluation in the future.